2017
DOI: 10.31989/ffhd.v7i4.354
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of blood pressure by aronia berries through inhibition of angiotensin-converting enzyme activity in the spontaneously hypertensive rat kidney

Abstract: Background: Aronia berries contain many important effects on potential health, with previous studies suggesting that aronia juice is useful for the treatment of hypertension.Objective: To examine whether aronia berries have improvement effects on hypertension through the inhibition of angiotensin-converting enzyme (ACE) activity.Method: The normal diet containing 10% freeze-dried aronia berries was administered to five spontaneously hypertensive rats (SHRs) in each group for 28 days, with their body weight, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…This is in line with the data that both Aronia berries and Aronia polyphenol extracts reduce quite effectively both SBP and DBP in spontaneously hypertensive rats [19]. The proposed mechanism might be through inhibition of the kidney renin-angiotensin system [20]. Others also found that A. melanocarpa extract decreases blood pressure in experimental model of hypertension [21,22].…”
Section: Discussionsupporting
confidence: 83%
“…This is in line with the data that both Aronia berries and Aronia polyphenol extracts reduce quite effectively both SBP and DBP in spontaneously hypertensive rats [19]. The proposed mechanism might be through inhibition of the kidney renin-angiotensin system [20]. Others also found that A. melanocarpa extract decreases blood pressure in experimental model of hypertension [21,22].…”
Section: Discussionsupporting
confidence: 83%
“…In studies conducted in spontaneously hypertensive rats a diet with 10% of lyophilised chokeberry reduced their blood pressure after three days [ 103 ] ( Table 2 ). However, a statistically significant reduction of the SBP occurred after 28 days.…”
Section: Influence Of Chokeberry On Hypertensionmentioning
confidence: 99%
“…Yamane et al (2017) administered a diet containing 10% freeze‐dried Aronia berries to spontaneously hypertensive rats for 28 days and found that blood pressure decreased in rats, as well as catalytic activity of ACE. They pointed out that the presence of cyanidin, cyanidin 3‐O‐glycoside, and quercetin 3‐O‐glycoside present in Aronia berries were effective in this regard.…”
Section: The Role Of Berries In Modulation Of Hypertensionmentioning
confidence: 99%